Influence of Service Quality on Muslim Customers’ Satisfaction towards Islamic Banking: A Study on Malaysian Islamic Banks - Uddin, Bashir; Shawon, Sayma Sadia; Asadullah, A B M (Global Disclosure of Economics and Business, 2017)
The purpose for this study is to explore the connection between consumer loyalty and five measurements of service quality in Islamic banks of Malaysia. This examination utilizes an example of 270 clients of Islamic banks; 175 reactions have been taken from every city like Kuala-Lumpur and Zohur Baru and Penang. Organized poll procedure has been utilized to gather information. The paper's discoveries uncover that Malaysian Islamic banks clients consider Trust, responsiveness, assurance as critical variables for consumer loyalty, then again, the elements of the service quality as the substantial is not emphatically noteworthiness as a measurements of fulfilment. Constraint of this examination is test size of the respondents. For the scholarly perspective, there is an incredible hugeness too an as professionals, administrators and approach creators can be discover the examples of consumer loyalty in the terms of administration quality for Islamic banks in Malaysia. The estimation of the present examination is specific since it is a measuring investigation of consumer loyalty and service quality measurements of Islamic banks in Malaysia.